Troponin T and Cardiac Enzyme Levels since Onset of Chest Pain in Patients Suspected of Acute Myocardial Infarction (AMI) in Punjab, Pakistan - Aslam Hayat, Ussama Munir, Zafar Iqbal, Hamid Mahmood, Khursheed Anwer, Shamila Afshan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To early diagnose the patients of AMI by using cardiac markers like CK, CK-MB, to find out the significance of these enzymes in comparison with high sensitive Troponin T hs and to find out the presence of a micro-infarction by using newly developed cTnT hs method. Patients and Methods: This was a cross sectional study, conducted at Punjab Institute of Cardiology and included 545 patients. Blood sample of every patient “Suspected of AMI” was sent to the laboratory for estimation of CK, CK-MB by conventional kit method and a high sensitive Troponin T reagent kit was used for prompt diagnosis of AMI. Patients of varying age were included and demographic details like hypertension, diabetes and smoking, family history of IHD, were collected to find out association with AMI. Results: Out of 545 study participants 62.65% (n=341) were male and 37.43% (n=204) were females, the mean age was 54.8 ± 13.42 years, the most frequent risk factor seen was hypertension (HTN in 72.0 % (n=90), followed by Smoking 45.5% (n=90), Diabetes mellitus (DM) 43.3% (n=90), and frequency of family history was seen 18.8% (n=90) in patients positive for acute myocardial infarction (AMI). 78.8% (n=90) males and 21.2%(n=90) females, indicated more prevalence of AMI in male population with frequency of AMI in patients from 41-60 years of age. There was significant association between hypertension, smoking and diabetes with AMI. Family history was not significantly associated with the incidence of AMI. CPK, CK-MB were performed on patient’s serum sample according to the procedures determined by reagent kits of Roche Diagnostic company on Chemistry Analyzer Hitachi 912. Optimized UV test method was used according to DGKC (German Society of Clinical Chemistry and Laboratory Medicine) and IFCC. Special Chemistry analyzer Cobas e 411, automated instrument was used for the quantitative measurement of Troponin T by using Chemiluminescence method (Troponin T hs reagent kits of Roche Diagnostic Company). Conclusion: It was concluded that a direct relationship exists between Troponin T and CPK, and CK-MB was more specific with even more closer and linear relationship with Troponin T hs. It was further observed that high sensitive Troponin T reagent method alone was sufficient to make a final diagnosis of AMI. Troponin T hs alone not only reduces the investigation time but reduces the overall cost as well. Keywords: Acute Myocardial Infarction.